2009
DOI: 10.1029/2008jd011307
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure of the low‐latitude mesospheric turbulence

Abstract: [1] Rocket-borne measurements of electron density were conducted from Sriharikota (13.7°N, 80.2°E) to study the fine structure of low-latitude mesospheric neutral turbulence. Spectra of electron density fluctuations were obtained using the continuous wavelet transform (CWT), and the turbulence parameters were estimated. The present study shows that turbulence is not present continuously in the mesosphere but exists in layers of different thicknesses varying from 100 m to 3 km, interspersed by regions of stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 40 publications
3
15
0
Order By: Relevance
“…The k H profile shown in Figure b also exhibits a general decrease with increasing altitude, from 52 m 2 s −1 at 85 km to 10 m 2 s −1 at 100 km, with a local maximum of 71 m 2 s −1 at 93 km. These measured k H values are generally consistent with the k z z values measured by other techniques in other latitudes [e.g., Lübken , ; Das et al , ; Bishop et al , ] and larger than the k z z values used in WACCM (Whole Atmosphere Community Climate Model) which has a maximum of about 20 m 2 s −1 [ Smith , , Figure 7]. ϵ was calculated based on equation and is shown in Figure c.…”
Section: Turbulence Heat Flux and Thermal Diffusion Coefficientsupporting
confidence: 81%
“…The k H profile shown in Figure b also exhibits a general decrease with increasing altitude, from 52 m 2 s −1 at 85 km to 10 m 2 s −1 at 100 km, with a local maximum of 71 m 2 s −1 at 93 km. These measured k H values are generally consistent with the k z z values measured by other techniques in other latitudes [e.g., Lübken , ; Das et al , ; Bishop et al , ] and larger than the k z z values used in WACCM (Whole Atmosphere Community Climate Model) which has a maximum of about 20 m 2 s −1 [ Smith , , Figure 7]. ϵ was calculated based on equation and is shown in Figure c.…”
Section: Turbulence Heat Flux and Thermal Diffusion Coefficientsupporting
confidence: 81%
“…If interpreted as turbulent echoes, they correspond to 20-200 mW kg −1 turbulent energy dissipation rates. Chandra et al (2008) and Uma Das et al (2009) reported energy dissipation rates of 1-100 mW kg −1 for the same altitude range, which were derived from the rocket measurements from Sriharikota located about 100 east of Gadanki. The LLME spectral widths for our three cases are close to those (2-3 m s −1 ) measured by Chandra et al (2008) with the same radar in July 2004.…”
Section: Discussionmentioning
confidence: 99%
“…The Heisenberg model exhibits these power laws, where a smooth transition takes place between them. We expect the possibility of neutral turbulence and dissipation in our system, which is revealed with the Heisenberg fit of different exponents shown in figure 10 [26]. The slopes obtained are -5/3 and -7, which give the turbulent and dissipative nature of the system respectively.…”
Section: Continuous Wavelet Transform (Cwt)mentioning
confidence: 99%